Throwing power and service life of galvanic cathodic protection with embedded discrete anodes for steel reinforcement in chloride contaminated concrete. (6th December 2021) - Van Belleghem, Bjorn; Maes, Mathias; Soetens, Tim
Highlights: Throwing power of GCP with discrete anodes measured accurately by potential mapping. Throwing power decreases with increasing chloride content in the concrete. Low temperature, high relative humidity and rainfall cause a higher throwing power. A strong relation was found between environmental temperature and galvanic current. A service life of 27 to 32 years was estimated for the discrete galvanic anodes. Abstract: The design of a galvanic cathodic protection (GCP) system with embedded discrete anodes for chloride contaminated reinforced concrete is greatly affected by the throwing power of the system. In this research, the influence of environmental conditions and corrosion activity of the steel reinforcement on the throwing power was investigated by means of depolarization measurements. Results show that the throwing power is highest in periods with rainfall, high relative humidity and low temperature and that it decreases with increasing chloride content in the concrete. Generally, GCP with discrete anodes is most effective when installed at the moment of corrosion initiation.